Why Some Sectors of Transition Economies are less Reformed than Others? The Case of Research and Education - Pavel Ciaian; Jan Pokrivcak (Economics and Econometrics Research Institute (EERI), 2005)
We analyze university research and education in transition countries. University system differs from industry in the nature of product that it produces. University system is engaged in production of public goods rather than private goods. The sector also suffers from measurement problem. We argue that because of these factors reforms were slower in this sector leading to low productivity growth. Lobby groups succeeded to gain significant control inside administrative structures regulating the sector. The case studies from the Czech Republic and Slovakia provide the evidence in support of this argument.
Keywords: I28; H11; P21; P5; 330; Research; education; public good; transition; reform; productivity